Sintesis Hidroksiapatit Dari Precipitated Calcium Carbonate (PCC) Cangkang Telur Ayam Melalui Proses Sol Gel Dengan Variasi pH Dan Waktu Aging - Alpina, Clara Shinta Asri; A, Yelmida; Zultiniar, Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Hydroxyapatite Ca10(PO 4)6(OH)2 is a compound of calcium phospate which is a bioactive, biocompatible and bioresourable. Hydroxyapatite (HAp) can be used as a bone implant,adsorbents and catalysts. Hydroxyapatite synthesis can be performed by using raw materials which is rich in calcium such as egg shell. Calcium in the form of Calcium Carbonate(CaCO3) on the chicken egg shell in this study changed to be precipitated Calcium Carbonate (PCC) through the process of carbonation. PCC from chicken egg shells used as a source of calcium in the synthesis of HAp with a sol gel method. In the synthesis of HAp, the varied of this method is pH (9; 10; and 11) and the aging time (24 hours; 48 hours; 72 hours). The analysis result of HAp synthesis with Fourier Transform Infrared Spectroscopy (FTIR) showed that the apatite compound has been formed with the absorption of PO4 3- ion at the wave number 1,025. .The highest transmittance obtained on the sample at the pH 9 aging time 24 hours; pH 9 aging time 48 hours and pH 9 aging time 72 hours. Based on X-ray Diffraction (XRD) analysis, the best HAp obtained in pH 9 aging time 72 hours with monoclinic crystal structure, with particle size was 53.89 nm. The result of SEMEDX analysis showed the morphological form agglomerate. The mole ratio of Ca and P hydroxyapatite from PCC of egg shell was 1.52 and 2.755 m 2/g surface area.Keywords: Precipitated Calcium Carbonate (PCC), Chicken Egg Shell, Hydroxyapatite, Sol gel Method, Aging Time